2006
DOI: 10.1002/meet.1450430129
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the performance of automatic new topic identification across multiple datasets

Abstract: Recent studies on automatic new topic identification in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Another observation is that the results obtained in this study also support the results published in a previous study [86]. The data set that has more topic shifts would be expected to be more successful in terms of shift-based measures.…”
supporting
confidence: 88%
“…Another observation is that the results obtained in this study also support the results published in a previous study [86]. The data set that has more topic shifts would be expected to be more successful in terms of shift-based measures.…”
supporting
confidence: 88%
“…We also use seven categories of search patterns in this study, which are as follows (Ozmutlu, H. et al , 2004, 2006a,b; Ozmutlu, S. et al , 2006), Ozmutlu and Cavdur (2005): Unique (new) . The second query has no common term compared to the first query:Example: Query j : Automobile.Query j+1 : Harry Potter. Next page (browsing) .…”
Section: Methodsmentioning
confidence: 99%
“…The researchers reported that topic shifts were estimated correctly, with a 77.8% precision in the overall database. Özmutlu, Çavdur, Spink, and Özmutlu (2005) have shown that one can train neural networks using multiple search logs. Özmutlu, Çavdur, and Özmutlu (2008) conducted a cross-validation of an artificial neural network application to automatically identify topic changes in Web search engine user sessions by using data logs of different Web search engines for training and testing the neural network.…”
Section: Review Of Literaturementioning
confidence: 99%